AUTOMATION, REMOTE CONTROL AND RELIABILITY OF THE LIGHTING SYSTEM OF MODERN CIVIL AVIATION AIRPORT - Ільєнко, C. C. (Science-based technologies, 2016)
One way to improve the safety of civil aircraft - it Automation categorized by the International Classification of aerodrome lighting systems. Automation is provided by the remote control of lighting to give the necessary signal to the system and its individual elements, in accordance with international regulatory and technical documentation for the equipment type. The level of reliability of the equipment, which is part of the automated control systems of the aerodrome lighting system, implemented at the level of design and production of the main manufacturers of the equipment and compliance with ICAO specifications and technical documentation. The analysis of modern automated lighting systems airfields with the help of programmable logic controllers and control using radio resources allowed us to determine the main directions of operation of the aerodrome lighting systems and ensure the safety of civil aviation on the ground